ส่วนประสมการตลาดที่มีผลต่อผู้บริโภคในการเลือก ร้านบุฟเฟ่ต์อาหารทะเล ในอำเภอเมืองเชียงใหม่ - ฐิติลักษณ์ คูหา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The purpose of this independent study was to study marketing mix factors affecting consumers on choosing seafood buffet in Mueang Chiang Mai District. The data was collected from 400 consumers in Mueang Chiang Mai, and was analyzed using descriptive statistics which consisted of frequency, percentage and mean. Inferential statistical analysis namely One-Way Analysis of Variance (One-Way ANOVA) was used to analyze the differences interns of age, monthly income and average cost per visit. Also multiple comparisons were used to analyse the data. The study found that the majority of questionnaire respondents were female, 21-30 years old. They were civil servants or state enterprise employees. They held Bachelor's degree and had an average income per month of 10,001-20,000 baht. They were single. For marketing mix factors, the respondents gave priority to service process the most and other factors were in the following order: product, price, people, physical evidence, place, and promotion. The respondents with different age and monthly income responded to marketing mix factors differently. While the respondents with different average cost per visit did not respond differently to the overall marketing mix factors, but responded differently to product, people and service process.